Dal Corpo-Prigione All’intelletto Attivo? Percorsi (e problemi) di trascendenza “virtuale” - Semplici, Stefano (Hermeneutica, 2020)
Virtual as an adjective is ever more permeating our lives. Every day, we are confronted with (we live as part of) virtual communities, virtual interactions with absolutely tangible effects (e-commerce, e-government), virtual reality. On the contrary, transcendence (transcendent) appears to be confined to a niche of academic interest and religious experience. This contribution aims at exploring the relationship between virtual and two patterns of transcendence (transcendent) that are often related to it, that is what we could call a (neo)platonic and a phenomenological approach to virtual reality. As for the first, some possible misunderstandings are addressed, in connection with the idea of a disembodied human sensoria and the ancient dream of “flying to heaven”. As for the second, the distinction real/reell and the notion of “transcendence in immanence”, as elaborated by Husserl, appears to play a pivotal role. Finally, Aristotle’s active intellect is introduced as a possible, provocative interpretation of some aspects of the new “reality” we are living in.